Инструменты диффузии инноваций в системе потребительской кооперации (Путеводитель предпринимателя, 2020)
Tools of innovation diffusion in the consumer cooperation system The trends of the development of Russian agro-industrial complex are considered, the elements of the innovation process are defined, a model of innovation for the agricultural consumer cooperative in order to improve efficiency and competitiveness is given.